A systematic review of symptomatic outcomes used in oesophagitis drug therapy trials. (13th April 2004) - Sharma, N; Donnellan, C; Preston, C; Delaney, B; Duckett, G; Moayyedi, P
Abstract : Symptoms are an important outcome for measurement in clinical trials into gastro-oesophageal reflux disease, but the optimal approach to symptom assessment has not been formally evaluated. The authors conducted a systematic review to assess how reflux symptoms have been evaluated and how well these correlate with oesophagitis healing and relapse.